Potential Fish Oil as Acute Hepatitis Candidate by Hepatoprotective Mechanism: A-review - Heru Sasongko; Muhammad Fiqri Zulpadly; Yeni Farida (Universitas Sebelas Maret, 2023)
Acute hepatitis is a health concern that emerged during the COVID-19 outbreak. Toxic drugs, infections, autoimmune diseases, and other causes may induce acute hepatitis, which is deadly. Acute hepatitis isn't treatable. Renewable natural products, such as fish, are used in complementary treatment. This paper mentions current preclinical and clinical studies of omega-3 fatty acids (N-3 FAs) for hepatoprotection. The mechanism of inhibition of oxidative stress and inflammation in the liver is the subject of discussion associated with its potential as a treatment for acute hepatitis. This review article on acute hepatitis treatment analyzed original articles, books, and other relevant material from the Web of Science, Scopus, and PubMed. The literature search was conducted in April-July 2022. The keywords explored during the literature investigation were